Political ecology as an approach for the geographical research on ecotourism in los Tuxtlas, Mexico - Neger, Christoph (2018)
The Los Tuxtlas region, one of the most biodiverse areas of Mexico, was declared a biosphere reserve in the year 1998. Since then, ecotourism has been promoted in the reserve, in order to promote both conservation and human development. While from an ecological point of view, it has had positive effects in some localities, ecotourism has not achieved to establish itself as an economically viable option for the local population. This limitation puts into question the sustainability of ecotourism in the area in general and inhibits that its ecological benefits could be extended further on the regional scale. In order to analyse the causes of this situation, the present investigation introduces the approach of political ecology, which allows it to analyse the role of external actors involved in multiple scales, assisting or hindering the development of ecotourism. The results are based on methods of qualitative fieldwork, particularly semi-structures interviews with local experts.